The biomass production and nutrient content of roselle leaves grown with poultry litter and Organosuper® - doi: 10.4025/actasciagron.v34i2.12754 (Acta Scientiarum. Agronomy, 2011)
The objective of this study was to evaluate the effects of poultry litter and Organosuper® with three modes of application on the biomass production and nutrient content of the leaves of roselle plants. The treatments in each crop cycle were in a factorial arrangement, 2 x 3 + 1, composed of a control and combinations of the two organic fertilizers (poultry litter (10 ton. ha-1) and Organosuper® (10 ton. ha-1) and the three application modes (surface, incorporated and surface + incorporated), in a randomized block design with four replicates. In the surface + incorporated mode, the organic fertilizers were applied as 5 ton. ha-1 surface and 5 ton. ha-1 incorporated. The highest productions of fresh and dry weight and number of calyxes were obtained for poultry litter in surface (10,776, 1,239 and 3,980,602 kg ha-1, respectively) and Organosuper® incorporated (11,372, 1,308 and 4,405,075 kg ha-1, respectively) in the agricultural year 2009/2010. The increases in the fresh and dry weights of the calyxes, leaves, stems and roots, number of calyxes, leaf area and fibers in the agricultural year 2008/2009 in the poultry litter treatments. Nutrients concentrations in the dry weight of the roselle leaves were not affected by the organic fertilizer type or by the mode of application.